Fatores associados à funcionalidade familiar de idosos na estratégia saúde da família - Silva, Alyne Andrade (2016)
Population aging and changes in the epidemiological profile of diseases, with a strongly hegemonic presence of chronic diseases, have an impact on the health of the elderly and influence changes in family structures, which are the main providers of the necessary care to elderly members who are more dependent. These factors interfere in the life aspects of the elderly and, above all, in family relationships. The way each family works will mean the best or worst care provided. Knowing this dynamics will aid in care planning for elderly people who are more dependent. Therefore, it was intended with this study to evaluate family functionality and associated factors of the elderly attended in the Family Health Strategy. This study was of the transversal and descriptive type with a quantitative approach. Data collection was performed at home through a structured interview with application of a form containing items on sociodemographic aspects, life habits, health conditions, functional evaluation scales of the elderly (ABVD and AIVD) and family functionality (Family APGAR). The data obtained were tabulated in Microsoft Excel 2011 and exported to Epi Info software version 7, where the statistical analysis of the work was performed. The Chi-square test (χ) 2, or Fisher's Exact, was used for the analysis of the association between categorical variables of interest and family functionality, considering a level of significance of 0.05. The study was approved by the Research Ethics Committee of the University of International Integration of Afro-Brazilian Lusophony, under the number of opinion 1269652. The study showed a predominance of females, 60 and 69 years of age and mean age of the sample of 70.4 years, with low income and low schooling, with the majority retired. They presented a mean of children of 4.7 (SD = 3.1). The majority of the elderly lived with spouses, with children and grandchildren, with an average of 3.1 (dp = 1.6). Regarding lifestyle habits, only 14.1% practiced regular physical activity, 66.6% had a history of smoking and 16.1% consumed alcoholic beverages. The elderly had regular self-perception of health (66.6%) and the most prevalent diseases were hypertension (60.6%) and Diabetes (39.3%). The majority used continuous medication (78.7%) and the most commonly used drugs were cardiovascular (60.6%). Regarding the perception of the elderly about their functional capacity, the majority presented independence for the ABVD (82.8%) and expressive partial dependence on the AIVD (40.4%). Regarding family functionality, the elderly had functional families (67.6%) and an important number of dysfunctional families (32.3%). There was no significant association between functional capacity and family functionality in this study. There was a significant association between age and AIVD classification (p = 0.0235) and between self-perception of health with family APGAR (p = 0.0006). It was also observed an association with significance between ABVD and AIVD variables (p = 0.024). Regarding the family APGAR domains, a higher frequency of responses was observed (16.1%), in the length of time the family shares with the elderly, when compared to the other dimensions. This may reveal the inexistence of a caregiver or the limited presence of the family, although the elderly live with relatives in most cases. It is believed that the findings of the present study may contribute to the FHT professionals to consider family dynamics and the factors associated with their functionality in planning and directing their actions, with the aim of safeguarding the health and quality of life of the elderly More dependent and contribute to the elaboration of future multidisciplinary interventions, such as the unique therapeutic project and family conferences, in order to qualify the family relations and to promote improvements in the care given to the elderly in their specificities.